OVERDENTURE SEBAGAI PERAWATAN PROSTODONTIK PREVENTIF: LAPORAN KASUS - Silvia Pridana; Syafrinani Syafrinani (Dentistry Faculty, 2017)
Teeth extractions are main reason of ridge resorption. Overdenture can give several benefits as preventive prosthodontic treatment which are (1) preservation of alveolar ridge height, (2) increase of denture stability, (3) maintainance of proprioceptive sensor, and (4) increase chewing efficiency. The aim of this case report is to explain overdenture as preventive prosthodontic treatment. A 65 years old male patient came to RSGMP FKG USU to make denture because he has problem in chewing food due to teeth lost. Intraoral examination showed complete edentulous on maxilla and remaining teeth 42 and 43 on mandibula. Intentional endodontic treatments followed by teeth preparation of 2 mm dome-shape with chamfer cervical margin were done for both remaining teeth as overdenture abutment, then covered with dome-shaped coping alloy to protect teeth from caries. Conventional complete denture was made for maxillary ridge and mandibular complete overdenture reinforced with metal meshwork was made. To reduce occlusal force that can cause ridge resorbtion denture were made with semianatomic artificial teeth. Complete overdenture is treatment of choice for this case to get biological and psychological benefits of preventive prosthodontic treatment. Keywords: Overdenture, dome shape, proprioception, preventive prosthodontic